EVALUATION OF THE LIMPAKUWUS PINE FOREST NATURAL TOURISM DEVELOPMENT PROGRAM IN BANYUMAS REGENCY - Rohid, Iid; Retnowati, Rita; Istiadi, Yossa (International Journal of Social Service and Research, 2025)
This study aims to evaluate whether the tourism program, implemented by Perum Perhutani/PT, is effective in enhancing economic opportunities and quality of life for residents. The study uses the CIPP (Context, Input, Process, Product) evaluation model, by analyzing primary data from natural tourism managers both by interviews and observations and secondary data (document collection) obtained from related agencies. The results of the research on environmental issues, legal frameworks, technical guidelines, funding sources, and the overall effectiveness of the program have provided added value for both parties. The conclusion from the study is that the cooperation program for the management of natural tourism objects in the Limpakuwus Pine Forest implemented by PT Palawi Risorsis with the LMDH has provided additional value for the two parties. This study provides a comprehensive analysis that complements existing literature while addressing its limitations.